1987
DOI: 10.1289/ehp.8772153
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological and experimental studies on the effects of methyl isocyanate on the course of pregnancy.

Abstract: Although press reports indicate that the leakage of methyl isocyanate (MIC) on December 3, 1984, in Bhopal has led to an increase in spontaneous abortions, stillbirths, infant mortality, and fetal abnormalities, no clinical or experimental studies on the reproductive toxicity of MIC were reported in scientific journals for several months after the accident. We therefore conducted, 9 months after the accident, a preliminary survey of 3270 families in Bhopal and experimental studies on the effects of MIC in preg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 8 publications
0
26
0
Order By: Relevance
“…An epidemiological survey by Varma showed that miscarriage and infant mortality were high in 865 gas exposed women who lived 1 km from the plant at the time of the gas leak. Results indicated that 43% of the pregnancies did not result in a live birth [14]. Of the 486 live births, 14% of those babies died during the 1st 30 days of life [14].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…An epidemiological survey by Varma showed that miscarriage and infant mortality were high in 865 gas exposed women who lived 1 km from the plant at the time of the gas leak. Results indicated that 43% of the pregnancies did not result in a live birth [14]. Of the 486 live births, 14% of those babies died during the 1st 30 days of life [14].…”
Section: Discussionmentioning
confidence: 98%
“…Results indicated that 43% of the pregnancies did not result in a live birth [14]. Of the 486 live births, 14% of those babies died during the 1st 30 days of life [14]. Clinicians at Bhopal have observed that now the girls who were exposed during their infancy and those in their mother's womb are experiencing 'menstrual chaos' [15].…”
Section: Discussionmentioning
confidence: 99%
“…In a preliminary epidemiological survey of the effect of the Bhopal accident on pregnant women living adjacent to the facility, Varma [12,13] reported a very high rate of unsuccessful pregnancies and a higher than normal infant mortality during the first 30 days of life. The data collected on 2566 pregnant and exposed women revealed a significant amount of pregnancy loss (18%), including 373 (15%) abortions and 82 (3%) stillbirths.…”
Section: Introductionmentioning
confidence: 99%
“…To test our hypothesis, we conducted a survey of 3,270 households adjacent to the Pesticide Plant in September 1985 [Varma, 1987]. In these household, 865 women reported to have been pregnant at the time of the gas leak but only 486 of them gave birth to live babies, which amounted to 43.8% pregnancy loss [Varma, 1987]. Another study of 2,566 pregnant women from 18,978 households also found pregnancy loss in 23.6% women as compared with 5.6% in 1,218 control cohorts [Bhandari et al, 1990].…”
Section: Introductionmentioning
confidence: 99%